Project management - Meredith, Jack R.; Shafer, Scott M.; Mantel, Samuel Jr (Wiley, 2018)
Projects continue to grow larger, increasingly strategic, and more complex, with greater collaboration, instant feedback, specialization, and an ever-expanding list of stakeholders. Now more than ever, effective project management is critical for the success of any deliverable, and the demand for qualified Project Managers has leapt into nearly all sectors. Project Management provides a robust grounding in essentials of the field using a managerial approach to both fundamental concepts and real-world practice.